UM INSTRUMENTO DE AVALIAÇÃO DO PROGRESSO FÍSICO DE UM PROJETO - Bezerra, Nelson Roberto de Albuquerque (2005)
The present work has as its objective to present a proposal instrument of evaluation give physical progress of a project management, focusing on the system of earned value, emphasizing the weekly physical progress of projects using the man hour as its unit of acting measure. After a study of the best theories in the area of Project Management, a bibliographical research was conducted which originated a comparison table of these practices, in the light of the practices of NBR ISO 10006(dec 2000), and the PMBOK 2004 3ª edition (a Guide book which encompasses all the theories regarding Project Management). The research worked with the models proposed by Limmer (1997) Heredia (1999) AND Kerzner (2003). The table which is proposed used a technique of progress management, through the use of some weekly monitored indicators along the project. This methodology aims at helping Project Managers to check the physical progress of the project and also to correct any possible mistake. After the suggestion of the table, a example was conducted with some adaptations in order to apply the suggested methodology to the elaboration of an Industrial Plan.